1.4k views
1 vote
B-2a^2/b^2-a/b^2-a where a=-3 and b=-1 answer should be in a improper fraction, if appropriate.

User Buzuosheng
by
4.9k points

1 Answer

1 vote

Answer:


\Rightarrow -(73)/(4)

Explanation:

The given expression,
(b-2a^2)/(b^2)-(a)/(b^2-a)

where, a = -3 and b = -1

Put the value of a and b into expression


\Rightarrow ((-1)-2(-3)^2)/((-1)^2)-((-3))/((-1)^2-(-3))

Simplify each parentheses


\Rightarrow (-1-18)/(1)+(3)/(1+3)


\Rightarrow -19+(3)/(4)

Now make same denominator


\Rightarrow -(76)/(4)+(3)/(4)


\Rightarrow (-76+3)/(4)


\Rightarrow -(73)/(4)

This is improper fraction because numerator is greater than denominator.

User Kingkong Jnr
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.